From clinical observations to molecular insights: Decoding immune checkpoint inhibitors‐induced prostatitis - Peng Luo; Ying Liu; Lan Xu; Zaoqu Liu; Linhui Wang; Hank Z. H. Wong; Quan Cheng; Anqi Lin; Xiao Fang; Aimin Jiang (View)
Abstract Immune checkpoint inhibitors (ICIs) have dramatically transformed cancer treatment; however, their impact on the male reproductive system remains poorly understood. This study aims to elucidate the incidence, risk factors, and molecular mechanisms underlying ICI‐associated prostatitis. We conducted an analysis of ICI‐associated prostatitis utilizing the U.S. Food and Drug Administration Adverse Event Reporting System (FAERS) database and evaluated risk through the application of the reporting odds ratio. A mouse model of ICI treatment was developed, and subsequent transcriptomic changes in prostate tissue were investigated using high‐throughput sequencing. Hematoxylin and eosin staining, immunohistochemistry, Von Frey testing, and enzyme‐linked immunosorbent assay were employed to confirm ICI‐induced prostatitis and further delineate its underlying mechanisms. Additionally, we investigated the therapeutic potential of specifically targeting interleukin‐6 (IL‐6) and extracellular signal‐regulated kinase (ERK) signaling pathways. FAERS analysis demonstrated a statistically significant positive correlation between ICI treatment and prostatitis risk (p < .05). In the murine model, ICI treatment induced an elevated inflammatory response in prostate tissue, characterized by enhanced inflammatory cell infiltration and upregulated expression of IL‐6 and tumor necrosis factor‐alpha. Transcriptomic analysis revealed significant activation of multiple inflammation‐related signaling pathways in prostate tissue following ICI treatment (false discovery rate < 0.05). Targeted inhibition of IL‐6 or ERK signaling pathways significantly attenuated ICI‐induced prostatitis symptoms, resulting in improved tissue pathology and decreased inflammatory factor expression (p < .01). This study delineates the characteristics and potential molecular mechanisms underlying ICI‐associated prostatitis, thereby establishing a theoretical foundation for the development of prevention and treatment strategies. Targeted modulation of IL‐6 and ERK signaling pathways may present novel therapeutic interventions for ICI‐associated prostatitis, thus warranting further clinical validation.